The Influence of Histological Subtype in Predicting Survival of Lung Cancer Patients with Spinal Metastases. Issue 1 (April 2016) - Kumar, Naresh; Tan, Kimberly-Anne; Tan, Jonathan; Zaw, Aye Sandar
Introduction: Lung cancer is one of the most common primaries responsible for spinal metastases. Recent advancements in systemic therapies for lung cancer have significantly improved the survival of patients with certain histological subtypes. Existing prognostic scoring systems have little to no prognostic value in lung cancer spinal metastases, and this may be due to the lack of consideration of lung cancer histology in their algorithms. Since prognostication plays a key role in the decision for operative management of spinal metastases, this study aims to analyze survival of lung cancer patients with spinal metastases according to different histological subtypes, to provide some guidance in making more informed surgical management decisions, better complementing recent medical oncologic advancements. Materials and Methods: All patients with histologically confirmed lung cancer treated for spinal metastases at our institution between May 2001 and April 2012 were retrospectively reviewed. The primary outcome measure was survival from the time of diagnosis. Survival data was obtained from the National Registry of Diseases Office. Patient demographic variables, lung cancer histology and various modalities of oncologic treatment were evaluated. Univariate and multivariate cox regression analyses of were performed using Stata v.12. Statistical significance was defined as p < 0.05. Results: Out of a total of 180 patients, 51 were treated surgically. The overall median survival time was 4.8 months, (range: 0.1–111.1 months). When subdivided according to histology, patients with non-small cell lung cancer (NSCLC) had a median survival of 5.2 (range: 0.1–111.1) months while patients with small cell lung cancer had a median survival of 2.4 (range: 0.1–11.9) months. Female gender ( p = 0.049), chinese ethnicity ( p = 0.040), NSCLC ( p < 0.001), treatment with epidermal growth factor receptor tyrosine kinase inhibitor (EGFR TKI) therapy ( p < 0.001), treatment with platinum doublet chemotherapy ( p < 0.001), and local radiotherapy ( p = 0.070) for spinal metastases were all significant good prognostic factors upon both univariate and multivariate analysis. Surgery for spinal metastases itself did not significantly improve survival ( p = 0.147). Conclusions: Female gender, chinese ethnicity, NSCLC, treatment with EGFR TKI therapy, treatment with platinum doublet chemotherapy, and local radiotherapy for spinal metastases are all independent favorable prognostic factors for patients with lung cancers spinal metastases. Profiling patients according to these factors should help guide decisions for surgical management of spinal metastases given that prognostic scoring systems are currently not predictive in this patient group.